Chemical file formats and line notations - Zielesny, Achim (Henry Stewart Talks, 2011)
Chemical structure representation, Atom positions in space, Redundant & Non-redundant connection tables, Atom numbering, MDL/Symyx molfile (.mol), Protein Data Bank (PDB) format, Daylight SMILES, Molecular tree and line notation, Chemical structure elucidation, 13C-NMR spectroscopy, HOSE code, Spectra prediction and spectra interpretation, Overlaying substructures, InChI, MARKUSH structures, Format conversion, OO programming, Unified Modelling Language (UML), Chemistry Development Kit (CDK)
Reviewed at 2022/04/12